2016
DOI: 10.3390/ma9110914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cu:Ag Atomic Ratio on the Properties of Sputtered Cu–Ag Alloy Thin Films

Abstract: Cu–Ag thin films with various atomic ratios were prepared using a co-sputtering technique, followed by rapid thermal annealing at various temperatures. The films’ structural, mechanical, and electrical properties were then characterized using X-ray diffractometry (XRD), atomic force microscopy (AFM), FESEM, nano-indentation, and TEM as functions of compositions and annealing conditions. In the as-deposited condition, the structure of these films transformed from a one-phase to a dual-phase state, and the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The calculated resistivities were 11 and 4.5 [μΩ cm] for the metastable phase and the eutectic point, respectively. The ratio between the resistivities, before and after the annealing, is in good agreement with previous study [ 19 ] where codeposition sputter is used to create metastable Cu–Ag phase for investigation (only thin layers, up to 1 μm can be achieved by sputter deposition technique).…”
Section: Resultssupporting
confidence: 91%
“…The calculated resistivities were 11 and 4.5 [μΩ cm] for the metastable phase and the eutectic point, respectively. The ratio between the resistivities, before and after the annealing, is in good agreement with previous study [ 19 ] where codeposition sputter is used to create metastable Cu–Ag phase for investigation (only thin layers, up to 1 μm can be achieved by sputter deposition technique).…”
Section: Resultssupporting
confidence: 91%
“…However, a detailed investigation of magnetic properties with an increase in nitrogen content has not been performed yet on flexible thin films, as reactive nitrogen sputtering may induce structural and magnetic changes. It is clear that processes, which occur at the surface during sputtering, critically affect the functional properties of as-deposited films [ 29 ]. Therefore, parameters such as grain size, the binding energies of surface atoms, and sputtering power will control the stoichiometry [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obvious diffraction peak in the (111) plane indicates that the film has a crystal structure. Hsieh [26] also reported that as-deposited Ag 50 Cu 50 film only has one diffraction peak. Compared with the reference, the similar XRD result could be obtained.…”
Section: Resultsmentioning
confidence: 94%